Labor Market Impacts and Responses : The Economic Consequences of a Marine Environmental Disaster - Hoang, Trung; Le, Duong Trung; Nguyen, Ha; Vuong, Nguyen Dinh Tuan (World Bank, Washington, DC, 2019)
This paper examines the labor market impacts of a large-scale marine environmental crisis caused by toxic chemical contamination in Vietnam's central coast in 2016. Combining labor force surveys with satellite data on fishing-boat detection, the analysis finds negative and heterogeneous impacts on fishery incomes and employment and uncovers interesting coping patterns. Satellite data suggest that upstream fishers traveled to safe fishing grounds, and thus bore lower income damage. Downstream fishers, instead, endured severe impact and were more likely to substitute fishery hours for working secondary jobs. The paper also finds evidence on an impact recovery to fishing intensity and fishery income, and a positive labor market spillover to freshwater fishery.